Editorial - Luciana Nedel (Journal on Interactive Systems)
It is my pleasure to introduce you the first issue of the SBC Journal on 3D Interactive Systems (JIS) in 2012. This issue contains three original papers, which surprisingly cover the same research topic, the development of virtual reality systems.